Performance Management, Rewards and Recognition, and Satisfaction of Employees on the Implementation of PRIME-HRM: A Partial Mediation Analysis - Roman, Adriel G.; Roman, Jessa A.; Valverde, Orlando T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The Program to Institutionalize Meritocracy and Excellence in Human Resource Management (PRIME-HRM) is a program of the Civil Service Commission promoting the culture of excellence in human resource management systems in the Philippines. However, little is known about the status of implementation of this program in the education sector. Thus, this research aims to explain the implementation of PRIME-HRM in the DepEd Division Offices in the Province of Laguna and its relationship to the level of satisfaction of the employees. It also tested the difference between the extent of program implementation when grouped according to their division, and the significant difference between the level of satisfaction of personnel on implementation of the program in each division office. A 7-point Likert scale (average Cronbach’s alpha of 0.973) instrument was floated to fifty respondents. Results showed that the extent of implementation of PRIME-HRM is very high. It was also noted the very high level of satisfaction of employees about PRIME-HRM implementation. Finally, the study concluded the mediation effects of rewards and recognition on the effects of the performance management pillar on the satisfaction of the employees.